181. Application of polyurethane foam cushion as a bolus material in the treatment of the Classic Kaposi's sarcoma. (December 2018) - Iacco, M.; Zucchetti, C.; Dipilato, A.C.; Lancellotta, V.; Saldi, S.; Aristei, C.; Tarducci, R.
Abstract: Purpose: Classical Kaposi's sarcoma (KS) was usually treated with large parallel and opposed photon beam. To spare muscles and bones, a patient with an extended KS (from limbs to fits on both legs) was treated with Helical Tomotherapy (HT). Because of the skin involvement two polyurethane foam cushions (PFC) were applied as immobilization device and as bolus material, in a "shell" configuration. Methods: The patient was positioned inside a PFC shell: the inner surface of the shell fitted the skin, in order to act as a bolus material. The CTV extended at least 5 mm inside legs; the PTV was the CTV expanded of 5 mm in all directions. A core structure distant 2 mm from the PTV was created for each leg and completely blocked in order to force HT to deliver only tangential beams to the PTV. The prescription was 60 Gy in 30 fraction; because of the length of target (1 m) the larger field width (5.02 cm), a pitch of 0.430, and a modulation factor of 2.0 were used. The irradiation time resulted in 15 min and the time required for the positioning and the MVCT was about 20 min. The surface doses was measured on the first session by means of EBT3 films: 24 films (2 cm × 2.5 cm) were placed all over the skin of the legs and feet. Results: The dosimetric results were reported in Table 1. The density of PFC was measured from the CT and resulted in 0.0066 g/cm 3 . The measured doses ranged from 83% to 94% with a mean value of 88% (1.75 Gy). Conclusions: In KS irradiation, the combination of a core blocked HT and the PSC shell offered an adequate dose coverage on the whole target, including the skin, spearing at the same time the muscles and skeleton.